2011
DOI: 10.1093/ejo/cjr136
|View full text |Cite
|
Sign up to set email alerts
|

Translation and validation of the Chinese version of the psychosocial impact of dental aesthetics questionnaire

Abstract: The psychosocial impact of dental aesthetics questionnaire (PIDAQ) could reflect dental aesthetic degrees evaluated by traditional dental aesthetic indices. However, no Chinese version of PIDAQ has been used. The aim of this study was to translate the original English version of PIDAQ into Chinese and to assess the validity and reliability of the Chinese version for application in Chinese young adults. The questionnaire was translated into Chinese, back translated, pre-tested, and cross-culturally adapted. Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 22 publications
6
63
0
1
Order By: Relevance
“…This questionnaire was validated for a Chinese population in previous studies and was judged valid and reliable. 26 The PIDAQ test measures three dimensions of psychosocial impacts, and is, simply, a reproducible, statistically easy test to use and can be completed in a short time. Studies about PIDAQ should be undertaken in patients undergoing oral restorative treatment in the anterior region 38 and implantation of missing anterior teeth is a very important restorative procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This questionnaire was validated for a Chinese population in previous studies and was judged valid and reliable. 26 The PIDAQ test measures three dimensions of psychosocial impacts, and is, simply, a reproducible, statistically easy test to use and can be completed in a short time. Studies about PIDAQ should be undertaken in patients undergoing oral restorative treatment in the anterior region 38 and implantation of missing anterior teeth is a very important restorative procedure.…”
Section: Discussionmentioning
confidence: 99%
“…25 Prior work has also shown that the translated Chinese version of PIDAQ demonstrates good reliability, validity and responsiveness. 26 The use of PIDAQ to assess the implant effects of missing anterior teeth…”
Section: Objectivementioning
confidence: 99%
“…Patient-based measures of oral esthetics has readily been developed and tested for responsiveness [17][18][19] The few [7][8][9]20] and no other professionally administered measure of oral esthetics than the PEI has been tested for responsiveness, which makes a comparison to other studies difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies had translated and culturally adapted the original English version into other language such as Portuguese 25 and Chinese. 26 Although there is a validated Chinese version of PIDAQ, 26 our version of Chinese PIDAQ was developed independently. Briefly, according to the procedure proposed by the International Quality of Life Assessment, 33 a pilot study similar to that of Sardenberg et al 25 was used to translate, back translate, and culturally adapt the original English version into Chinese.…”
Section: Self-reported Questionnairementioning
confidence: 99%
“…Previous studies have confirmed its validity in different countries with different languages. [25][26][27] On the other hand, the method by which malocclusion is defined is important in studies evaluating OHRQoL with respect to malocclusion. Although previous studies frequently used the Dental Aesthetic Index (DAI) [9][10][11]21,25 and Index of Orthodontic Treatment Need (IOTN) 8,23,24,[28][29][30] to define malocclusion, Angle's Classification is most widely used to define malocclusion clinically.…”
Section: Introductionmentioning
confidence: 99%